2011
DOI: 10.1080/19315260.2011.565113
|View full text |Cite
|
Sign up to set email alerts
|

Cauliflower Plant Organ Water Status and Nitrogen Translocation From Leaf–Stem Sources to Head Sinks in Its Three Hybrid Cultivars

Abstract: Cauliflower's (Brassica oleracea var. botrytis L.) fresh appearance and high nutritional values may be related to plant organ water holding and nitrogen (N) translocation from leaf-stem sources to head sinks. Cauliflower plant water and N nutrition relations were examined in a two-site field study in Nova Scotia. The objectives of this study were to assess cauliflower plant organ water and N translocation efficiency and to quantify the correlations between cauliflower plant organ water status, N translocation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…At harvest, the nitrogen concentration is higher in florets than leaf-stem. In our study, the highest protein content was observed in florets, but the difference between florets and leaf-stem was not as big as suggested by Hong [40]. However, the decrease in nitrogen was reported with the increase of the organ size [39,40].…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…At harvest, the nitrogen concentration is higher in florets than leaf-stem. In our study, the highest protein content was observed in florets, but the difference between florets and leaf-stem was not as big as suggested by Hong [40]. However, the decrease in nitrogen was reported with the increase of the organ size [39,40].…”
Section: Discussionsupporting
confidence: 44%
“…In our study, the highest protein content was observed in florets, but the difference between florets and leaf-stem was not as big as suggested by Hong [40]. However, the decrease in nitrogen was reported with the increase of the organ size [39,40]. Thus, the lower protein concentration in florets can be related to its dilution in the vegetable tissue at the harvest stage.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Like in cauliflower leaves, the head also contains significant amounts of phytochemicals and antioxidants [ 64 ]. However, the fresh appearance of cauliflower’s head and its reasonably promising nutrition levels have been reported to be attributable to plant part water holding capacity and translocation of essential mineral elements including primarily N [ 65 , 66 ]. In fact, N plays a vital role in the synthesis of a variety of amino acids, vitamins and proteins and thus it determines the yield and quality of the cauliflower crop [ 65 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the fresh appearance of cauliflower’s head and its reasonably promising nutrition levels have been reported to be attributable to plant part water holding capacity and translocation of essential mineral elements including primarily N [ 65 , 66 ]. In fact, N plays a vital role in the synthesis of a variety of amino acids, vitamins and proteins and thus it determines the yield and quality of the cauliflower crop [ 65 , 67 , 68 ]. Like several other inorganic nutrients, an optimal N translocation from the shoot (source) to the head (sink) is believed to determine nutritional quality of cauliflower [ 65 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%